Pengaruh Reputasi, Kualitas Informasi Dan E-WOM Terhadap Minat Beli Pada Situs Jual Beli Online Lazada di SMA Negeri 1 Kraksaan Probolinggo (Studi Pada SMA Negeri 1 Kraksaan Probolinggo) - Ikhlashi, Bunga; Nurhajati, Nurhajati; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to test and determine the influence of reputation, information quality, and e-wom on buying interest on the Lazada online buying and selling site in Probolinggo (Study at SMA Negeri 1 Kraksan). This research is a type of quantitative research. The sampling technique used the Malhotra formula with calculated results of 100 samples. To solve the problems in this research, SPSS was used with validity tests, reliability tests, normality tests, multiple linear regression analysis, multicollinearity tests, heteroscedasticity tests, F tests, and t tests. The research results show that simultaneously the variables Reputation (X1), Information Quality (X2), and E-wom (X3) have a significant effect on Purchase Interest (Y). Partial research results show that Reputation (X1), Information Quality (X2) and E-wom partially have a significant effect on Purchase Interest (Y). Keywords: Reputation, Information Quality, E-wom, Purchase Interest.